ANALISIS FAKTOR FUNDAMENTAL YANG MEMPENRAUHI RETURN PERUSAHAAN RITEL - Heri Sasono; Muhammad Hendra Apriwarto (Pusat Riset dan Inovasi Nasional, 2022)
The company's performance can be seen from the profitability and sustainability in maintaining its business, especially retail companies. The purpose of this study was to examine the influence of factors that affect the performance of retail companies, such as DER, NPM and TATO. The population of this research is 25 companies and the research sample is 8 companies on the Indonesia Stock Exchange (IDX).The research method uses Normality Test, t test, Anova test, Coefficient of Determinants, Correlation and Multiple Linear Regression using SPSS software version 22. The results of the research Net Profit Margin (NPM) and Total Asset Turnover (TATO) have a significant effect on Return on Assets (ROA), while the Debt Equity Ratio (DER) has no significant effect. However, simultaneously the three independent variables (DER, NPM and TATO) have a significant effect on Return on Assets with the equation Y = -0.015 - 0.001X1 + 1.549X2 + 0.011X3.